Dermoscopy Of Onychomycosis: A Literature Review - Primisawitri, Pratiwi Prasetya; Mulianto, Nurrachmat (Rumah Sakit Umum Daerah Dr. Moewardi, 2024)
Background: Onychomycosis is a fungal infection of the nails. Onychomycosis is caused by dermatophytes, non-dermatophyte molds, and non-dermatophyte fungi. Dermoscopy examination has gradually been used as a modern diagnostic method to assess non-invasive nail abnormalities that are easy and inexpensive to visualize abnormal microscopic features of the nail. However, it is still uncommon for medical personnel to diagnose onychomycosis using dermoscopy. Purpose: To provide information on the benefits of the nail dermoscopy technique that can diagnose onychomycosis and describe observable dermoscopic findings. Results: Dermoscopy findings on onychomycosis showed a diverse picture depending on the type. Distal and lateral subungual onychomycosis shows the proximal margin of the onycholytic area with spikes leading to proximal folds and longitudinal striae. White superficial onychomycosis shows large, brittle, irregularly spreading white-yellow patches on the nail's surface. Proximal subungual onychomycosis has one or more transverse white bands on the inner nail plate, while total dystrophic onychomycosis shows longitudinal striae and spikes and irregular distal terminations. Conclusion: Nail dermoscopy improves quality and simplifies examination to establish the diagnosis of onychomycosis because it can guide clinicians in conducting screening, choosing the best time for mycological sampling, and making therapeutic decisions.